Economic profile of Uttaranchal - Krishna, Sridhar (2002)
The first states reorganisation commission had turned down the proposal for the creation of Uttaranchal on the grounds that it was not economically viable. The backward, agrarian character in the state, with fragmented and uneconomical landholdings, would seem to bear out this conclusion. However, with stress on diversification from agriculture to horticulture, investment in irrigation, infrastructure and promotion of tourism, Uttaranchal can be made viable.- Reproduced.
Keywords: Economic and social development